Rethinking Antillothrix: The Mandible and Its Implications. Issue 8 (25th June 2013) - Rosenberger, Alfred L.; Klukkert, Zachary S.; Cooke, Siobhán B.; Rímoli, Renato
Abstract A mandible of the Hispaniolan primate Antillothrix bernensis, virtually complete and providing the only definitive evidence of the species' lower dentition, has been discovered in a submerged Dominican Republic cave. The new specimen enables a more certain assessment of the species' phylogenetic position than previously possible. It belongs to the same individual as the nearly complete young adult cranium and postrcranial elements found earlier at the same site. Of the extinct Caribbean platyrrhines, the jaw compares well with partial mandibles representing Xenothrix mcgregori, from Jamaica. Among living platyrrhines, it closely resembles Callicebus and Aotus, as documented in a biometric analysis employing three‐dimensional geometric morphometrics of Callicebus, Aotus, Pithecia, Chiropotes, Cacajao, Cebus, and Saimiri. The jaw falls within the morphological variability of Callicebus and Aotus in this three‐dimensional analysis, is otherwise most similar to Pithecia, and is distinct from cebines. Lower molars resemble the Haitian primate, Insulacebus, a genus known by a full dentition and gnathic fragments with a pattern of derived features also present in Xenothrix. Considering the available craniodental and postcranial evidence, we conclude that Antillothrix is not properly classified as cebid but rather is best grouped with Pitheciidae, an idea long central to discussions of the phylogenetic affinities of the Greater Antillean primates. Since Antillothrix and Insulacebus are more primitive anatomically than the highly modified Xenothrix, it is tempting to surmise that the origins of the latter involved a vicariance or dispersal event via Hispaniola isolating it on Jamaica. Am. J. Primatol. 75:825–836, 2013. © 2013 Wiley Periodicals, Inc.